2022
DOI: 10.1093/bjsw/bcac094
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Learning from the Mindfulness-based Social Work and Self-care Programme to Social Work Student Practice during COVID-19: A Qualitative Study

Abstract: This is the first study which has explored how social work students have applied the learning from a bespoke Mindfulness-Based Social Work and Self-Care (MBSWSC) programme to their social work practice. A qualitative research design was chosen, and a realist ontological position taken. The qualitative data were collected from reflective journals from seven social work students on placement who had completed the MBSWSC programme. An inductive thematic and comparative analysis methodology was used to identify ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This is also directly in line with Maddock (2023)'s theory of how mindfulness-based practices can improve social worker self-care and reflective social work practice. The finding that the social workers in this study experienced increased empathy and compassion, which allowed them to connect more directly with service users, and the issues that were important to them, is supported by Maddock et al (2022c). Maddock et al (2022c) explored how social work students applied the learning from the MBSWSC programme to their social work practice placements using student reflective journals.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This is also directly in line with Maddock (2023)'s theory of how mindfulness-based practices can improve social worker self-care and reflective social work practice. The finding that the social workers in this study experienced increased empathy and compassion, which allowed them to connect more directly with service users, and the issues that were important to them, is supported by Maddock et al (2022c). Maddock et al (2022c) explored how social work students applied the learning from the MBSWSC programme to their social work practice placements using student reflective journals.…”
Section: Discussionmentioning
confidence: 61%
“…The finding that the social workers in this study experienced increased empathy and compassion, which allowed them to connect more directly with service users, and the issues that were important to them, is supported by Maddock et al (2022c). Maddock et al (2022c) explored how social work students applied the learning from the MBSWSC programme to their social work practice placements using student reflective journals. Maddock et al (2022c) found that the increased self-awareness, empathy, compassion, and capacities for reflection and reflexivity that the students experienced during their social work practice placements, allowed them to be more cognisant of the service user needs and the impact of their environment of them e.g.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Fodor, S. et al discuss the importance of education in the development of skills and literacy needed in the labor market and devise a method of job screening, with text mining techniques as the underlying logic, to help the labor market to match labor supply and demand [15]. Alan, M. et al described positive thinking nursing programs used to assist college graduates new to social work, noting the role of these programs in helping students develop sustainable learning and improve practice [16]. Audrey, R. et al examined students' views and attitudes toward social internships and found that students valued social internships as necessary for their future work and professional studies [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, students' experiences highlight the increased flexibility with more challenges, autonomy, developing specific skills and missing out few, and driving self‐learning with such e‐placements. The available literature underlines various innovations and changes in field education across the globe due to COVID‐19 (Azman et al, 2020 ; Golightley & Holloway, 2020b ; Henley et al, 2021 ; Lomas et al, 2022 ; Maddock, & McCusker, 2022 ; McFadden et al, 2020 ). These include both digital and field‐based innovations.…”
Section: Introductionmentioning
confidence: 99%